Evolving dimensions of women’s empowerment in India - Bharti Singh; Shri K. Singh (PLoS ONE, 2025)
Empowerment is a dynamic, multifaceted concept shaped by intersecting socio-economic, cultural, and demographic contexts. The conceptualization of women’s empowerment has evolved from ensuring basic rights, such as education and employment, to addressing complexities that secure women’s rightful place in society, reflecting cultural and historical struggles for equality and inclusion. This study explores the evolving dimensions of women’s empowerment in India from 2006 to 2021, using data from three recent rounds of the National Family Health Survey. We employed Confirmatory Factor Analysis to investigate changes in the different dimensions of women’s empowerment and develop a robust empowerment index. To understand the effect of socio-economic factors on women’s empowerment, we conducted a Multinomial Logistic Regression analysis. Furthermore, Age-Period-Cohort (APC) analysis was performed to capture temporal and generational evolution of women’s empowerment and its dimensions. Our analysis revealed shifts in key dimensions of women’s empowerment over time. In 2005–06, “Freedom of Mobility” emerged as the dominant dimension, whereas “Financial Independence” became prominent in 2015–16, and “Attitude towards Violence” took precedence by 2019–21. During 2005–06, older women (40–49 years) exhibited a higher level of empowerment compared to younger women (15–30 years). However, by 2015–16, the concentration of more empowered women shifted to younger women (25–35 years). APC analysis indicated that age plays a significant role in women’s empowerment, with women approximately 30 years of age exhibiting the highest levels of empowerment. Additionally, older cohorts (born before 1970) showed no significant effects on empowerment. In contrast, cohorts born after 1970 demonstrated a significant impact.